(untitled) (International journal of medical sciences, 2026)
This article analyzes the scientific-theoretical foundations, advantages, and practical outcomes of the digitalization of the healthcare system, as well as the use of artificial intelligence (AI) technologies in this process. It discusses the introduction of digital technologies into the medical field, their stages of development, and areas of application. The article provides a comparative analysis of the digitalization processes in the healthcare systems of South Korea and Uzbekistan, identifying their similarities and differences. The analysis also covers the strengthening of digital infrastructure, improving the digital competencies of medical professionals, standardization trends of AI-based medical equipment, and the policy prospects of foreign countries in this area. The article includes analyses and examples illustrating the current stage of digital infrastructure development in today’s healthcare system. In addition, the article thoroughly examines the impact of AI technologies on changes in the field of medical devices, as well as their role and significance in the healthcare industry.